Adrenocortical and Adipose Responses to High-Altitude-Induced, Long-Term Hypoxia in the Ovine Fetus - Dean A. Myers; Charles A. Ducsay (Hindawi Limited, 2012)
By late gestation, the maturing hypothalamo-pituitary-adrenal (HPA) axis aids the fetus in responding to stress. Hypoxia represents a significant threat to the fetus accompanying situations such as preeclampsia, smoking, high altitude, and preterm labor. We developed a model of high-altitude (3,820 m), long-term hypoxia (LTH) in pregnant sheep. We describe the impact of LTH on the fetal HPA axis at the level of the hypothalamic paraventricular nucleus (PVN), anterior pituitary corticotrope, and adrenal cortex. At the PVN and anterior pituitary, the responses to LTH are consistent with hypoxia being a potent activator of the HPA axis and potentially maladaptive, while the adrenocortical response to LTH appears to be primarily adaptive. We discuss mechanisms involved in the delicate balance between these seemingly opposing responses that preserve the normal ontogenic rise in fetal plasma cortisol essential for organ maturation and in this species, birth. Further, we examine the response to, and ramifications of, an acute secondary stressor in the LTH fetus. We provide an integrative model on the potential role of adipose in modulating these responses to LTH. Integration of these adaptive responses to LTH plays a key role in promoting normal fetal growth and development under conditions of a chronic stress.